Human Bone Marrow Mesenchymal Stem Cells Promote Gastric Cancer Growth via Regulating c-Myc - Bin Chen; Jing Yu; Qianqian Wang; Yuanyuan Zhao; Li Sun; Changgen Xu; Xiangdong Zhao; Bo Shen; Mei Wang; Wenrong Xu; Wei Zhu (Stem Cells International)
The clinical application of human bone marrow mesenchymal stem cells (hBM-MSCs) has generated a great deal of interest because of their potential use in regenerative medicine and tissue engineering. However, safety concerns over hBM-MSCs limit their clinical application. In this study, we observed that hBM-MSC-conditioned medium (hBM-MSC-CM) promotes gastric cancer development via upregulation of c-Myc. Our results showed that c-Myc was upregulated in MGC-803 and BGC-823 cells after hBM-MSC-CM treatment. Moreover, we found that the c-Myc inhibitor JQ1 and c-Myc siRNA decreased the expression of c-Myc in hBM-MSC-CM-treated tumor cells in vitro. Additionally, hBM-MSC-CM enhanced the migration and glucose uptake of gastric cancer cells. In vivo studies showed that JQ1 inhibited hBM-MSC-CM-induced gastric cancer growth. These results indicated that hBM-MSC-CM induced gastric cancer growth via upregulation of c-Myc, which may be a potential risk factor and/or a therapeutic target for clinical applications.